2017
DOI: 10.1038/tp.2017.91
|View full text |Cite
|
Sign up to set email alerts
|

Molecular indicators of stress-induced neuroinflammation in a mouse model simulating features of post-traumatic stress disorder

Abstract: A social-stress mouse model was used to simulate features of post-traumatic stress disorder (PTSD). The model involved exposure of an intruder (male C57BL/6) mouse to a resident aggressor (male SJL) mouse for 5 or 10 consecutive days. Transcriptome changes in brain regions (hippocampus, amygdala, medial prefrontal cortex and hemibrain), blood and spleen as well as epigenome changes in the hemibrain were assayed after 1- and 10-day intervals following the 5-day trauma or after 1- and 42-day intervals following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 62 publications
1
61
0
1
Order By: Relevance
“…Molecular and phenotypic data have shown that aggressor exposure produced significant stress effects that persisted (Gautam et al, ; Hammamieh et al, ; Muhie et al, ; Muhie et al, ). This study was to characterize the composition of the fecal microbiome during the stress exposure of 6 h daily for 10 days and the fecal samples from control or Agg‐E C57BL/6J mice were analyzed for 16S rRNA sequences.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular and phenotypic data have shown that aggressor exposure produced significant stress effects that persisted (Gautam et al, ; Hammamieh et al, ; Muhie et al, ; Muhie et al, ). This study was to characterize the composition of the fecal microbiome during the stress exposure of 6 h daily for 10 days and the fecal samples from control or Agg‐E C57BL/6J mice were analyzed for 16S rRNA sequences.…”
Section: Resultsmentioning
confidence: 99%
“…The stress-sensitive gene regulatory index performs as required for such a diagnostic test, since it responds in a dose-dependent way to stress exposure, is independent of the modality of stress exposure, and is precise, even while relying on a relatively small number of measured variables. A practical diagnostic test in humans would necessarily use tissues that can be easily biopsied such as peripheral blood mononuclear or buccal cells, which also show stress-induced changes in gene regulatory function (5,6,47,48). A. MA plots of RNA sequencing data from adrenal gland for animals exposed to the chronic variable stress (CVS) or chronic shock (CS) protocols.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of traumatic stress exposure are encoded in both the gene regulatory and neural networks of individuals subjected to stress (3)(4)(5). One approach to developing molecular diagnostic tools is to use changes in gene regulatory function as markers of stress exposure (6). The gene regulatory network integrates a large number of different signals in order to yield a particular pattern of gene expression (7).…”
Section: Introductionmentioning
confidence: 99%
“…After screening, the expression profile number GSE68077 was retrieved based on GPL7202 platform Agilent-014868 Whole Mouse Genome Microarray 4x44K G4122F for our analysis (Muhie, et al, 2017).…”
Section: Datasets Of Mrnas and Lncrnasmentioning
confidence: 99%